The problem of peace and the meaning of 'post-war'. Issue 3 (4th May 2018) - Klem, Bart
Abstract: The literature on war endings and peace-building pivots on a concept that it in fact continues to struggle with: peace. I argue that we should abandon the conceptualisation of peace as a condition. By implication, we must also abandon the notion of war-to-peace transition and the underlying teleology that projects peace as a deferred and ambiguous end state. Instead, I propose the term post-war transition. Importantly, the prefix post should not be understood as a temporal breakpoint: a definitive after. Rather, it signals an ambition to address and move beyond, analogous to the term post-colonialism. I subsequently draw on the post-colonial literature to further elaborate my conceptualisation of post-war transition with three propositions, respectively concerning: the discursive politics of retrospectivity; the assertion of sovereignty as the foundational referent of law and political order; and the concept of articulation to juxtapose contingent change and constrained agency. I then apply these ideas to the Sri Lankan case to illustrate what angles and insights my conceptualisation of post-war transition could offer.